Influence of phase and dominance on ground reaction forces and upper extremity muscle activity during the modified-Closed Kinetic Chain Upper Extremity Stability Test - T. De Sousa; Y. Blache; M. Degot; I. Rogowski (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background The Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST) is a physical performance test designed to assess the upper extremity (UE) stability. However, only one outcome measure is provided for both UEs, limiting its application if the UEs are not similarly involved. Moreover, the changes in loads sustained by the support UE throughout the movement may influence the support UE stability. Additional knowledge on the underpinning biomechanical mechanics of the performance is therefore needed to better understand how to use the measure of the CKCUEST to design the athlete’s physical ability development or recovery. This study aimed to investigate the influence of phase and dominance on kinetic and support UE muscular demand during a modified-CKCUEST touch. Methods Twenty-five male multisport athletes (age: 26.0 ± 11.3 years; mass: 77.8 ± 23.3 kg; height: 179.0 ± 6.5 cm) performed the modified-CKCUEST, i.e. hands at half span apart. The ground reaction forces (GRF) and activity of eight perihumeral and scapulothoracic muscles of support UE were recorded and analyzed according to the UE dominance and phase (takeoff vs. landing). Statistical non-Parametric Mapping analyses were used to assess the effects of dominance and phase on the support UE GRF and the effects of dominance, phase, and muscle on the support UE muscle activity. Results The scapulothoracic and perihumeral muscles of the support UE were activated at low-to-very-high levels during the modified-CKCUEST touch. Variations in muscular activity over a touch were required to sustain variations in loads in medial, vertical, and posterior directions. Lower loads were observed during the takeoff phase than those during the landing phase (p < 0.05). Despite similar muscular activities in both UEs, the dominant UE sustained higher medial loads than the non-dominant UE (p < 0.05), while opposite results were observed for posterior loads (p < 0.05). Conclusions The modified-CKCUEST involves similar muscle activity of the support UE in response to varying loads sustained in different directions according to dominance. The quantitative assessment provided by the modified-CKCUEST score may be complemented by a qualitative observation of body displacements, allowing coaches and clinicians to identify limitations in the stability of the UEs.